Culicoides biting midges (Diptera, Ceratopogonidae) in various climatic zones of Russia and adjacent lands. Issue 2 (December 2014) - Sprygin, A.V.; Fiodorova, O.A.; Babin, Yu. Yu; Elatkin, N.P.; Mathieu, B.; England, M.E.; Kononov, A.V.
ABSTRACT Culicoides biting midges play an important role in the epidemiology of many vector‐borne infections, including bluetongue virus, an internationally important virus of ruminants. The territory of the Russian Federation includes regions with diverse climatic conditions and a wide range of habitats suitable for Culicoides. This review summarizes available data on Culicoides studied in the Russian Federation covering geographically different regions, as well as findings from adjacent countries. Previous literature on species composition, ranges of dominant species, breeding sites, and host preferences is reviewed and suggestions made for future studies to elucidate vector‐virus relationships.